COST CALCULATION IN GEOLOGICAL EXPLORATION WORK (International Congress on Economics, Management and Business Studies, 2026)
The article outlines the specific features of cost accounting in geological exploration work, the procedures for classifying costs, and the accounting procedures. Scientific proposals and practical recommendations for improving cost management in the geology sector have been developed.